2015
DOI: 10.1038/jid.2015.230
|View full text |Cite
|
Sign up to set email alerts
|

Acute Inhibition of MEK Suppresses Congenital Melanocytic Nevus Syndrome in a Murine Model Driven by Activated NRAS and Wnt Signaling

Abstract: Given that psoriasis is increasingly recognized to be associated with comorbid conditions of obesity, diabetes, metabolic dysregulation, and cardiovascular diseases that may be related to inflammation in skin (Davidovici et al., 2010), it is of interest that associated functional pathways were also identified through IPA, including metabolic disease and cardiovascular disease (Supplementary Figure S1b online), leading to two potential mechanisms for increased association between psoriasis and metabolic and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Animal model data of mitogen-activated protein kinase kinase (MEK) inhibitor use has recently demonstrated an attenuation of leptomeningeal disease in a murine model of CMN syndrome. 46 As a result we have used the MEK inhibitor trametinib as therapy in a small series of four patients with NRAS-mutated CNS melanoma (three of whom had CMN). 47 This demonstrated measurable and objective relief of symptoms and signs in all patients, although to varying degrees.…”
Section: Melanoma Managementmentioning
confidence: 99%
“…Animal model data of mitogen-activated protein kinase kinase (MEK) inhibitor use has recently demonstrated an attenuation of leptomeningeal disease in a murine model of CMN syndrome. 46 As a result we have used the MEK inhibitor trametinib as therapy in a small series of four patients with NRAS-mutated CNS melanoma (three of whom had CMN). 47 This demonstrated measurable and objective relief of symptoms and signs in all patients, although to varying degrees.…”
Section: Melanoma Managementmentioning
confidence: 99%
“…Based on these data, they proposed a new lgCMN management strategy involving the use of injection-based targeted therapies to treat unresectable lesions and reduce lgCMN burden prior to surgery. In support of the therapeutic strategy put forth by Rouille et al 2019, Pawlikowski et al showed that the MEK inhibitor, selumetinib, can limit the extent of cutaneous and central nervous system disease in an NRASmutant, Apc-null CMN mouse model (Pawlikowski et al, 2015). Early clinical data also suggest a role for MEK inhibitors in controlling human lgCMN.…”
Section: The Promise Of Targeted Therapy In Lgcmnmentioning
confidence: 95%
“…In the first model, the melanocytic expression of NRas 12D leads to leptomeningeal hyperpigmentation and subsequent melanoma formation (Pedersen et al, 2013). In the second model, the expression of NRas 61R , in combination with activated WNT signaling (Apc loss), causes the mice to develop leptomeningeal melanosis (Pawlikowski et al, 2015). Still, whether the cutaneous and central nervous system lesions that develop in these models fully recapitulate the genetic and pathological heterogeneity of human CMN remains unclear.…”
Section: A New Preclinical Model Of Lgcmnmentioning
confidence: 99%
“…transgenic mice carrying melanocyte-specific oncogenic mutations develop dermal melanocytic proliferations reminiscent of human congenital or blue nevi (e.g. Dhomen et al, 2009;Pawlikowski et al, 2015;Shakhova et al, 2012). The development and size of these lesions can be dramatically altered with genetic engineering that results in changes in expression of stem cell or hepatocyte growth factor from keratinocytes (Kunisada et al, 1998(Kunisada et al, , 2000 or increased Wnt signaling within melanocytes (Pawlikowski et al, 2013).…”
Section: Significancementioning
confidence: 99%